The level of health awareness among young people in light of the war on Syria, a case study: Daraa Governorate (Damascus University Journal of arts and humanities sciences, 2025)
The research aimed to identify the level of health awareness among young people in light of the war on Syria. The research adopted the descriptive analytical method, the social survey method, and the questionnaire was used as a data collection tool. The original research community consisted of young people of Syrian nationality between the ages of 18-34 years, residing in Daraa Governorate during the period of conducting the research. The sample size, which was taken according to the intentional sampling method, was (200) respondents. on the statistical analysis of the data carried out through the statistical program (SPSS) Using percentages, a number ofresults were reached that indicate, in their entirety, the existence of negative effects of the war on Syria in most of the sample units (health awareness in the field of food, and the field of personal health). As well as its impact on some sources of health information.
Keywords: consciousness; Health consciousness; Level of health awareness; The war on Syria; Youth.